Koordinasi Bappeda dalam Perencanaan Pembangunan Kesehatan di Kabupaten Enrekang - Agusman Hidayat; Juanda Nawawi; Rabina Yunus (Departemen Ilmu Pemerintahan Fisip Unhas, 2011)
Abstract: This study aims to identify and describe how the coordination form of BAPPEDA with the Department of Health in the health development planning in Enrekang. Factors that influencing the coordination BAPPEDA with the health department, as well as to identify and describe the health development planning process at the district Enrekang. The type of research that used are descriptive and qualitative methods, in an attempt to illustrate, describe, express, explain, and analyze BAPPEDA coordination in health development planning. Data collection techniques used were interviews and direct observation, and survey research base used. The results showed that a form of coordination of BAPPEDA in health planning in Enrekang is coordination in planning consist of the meeting and briefing, sharing the information and building the comitmen beetwen all of stakeholders. And health development planning process is the preparation of plans, preparation of program planning, program implementation, monitoring and evaluating the implementation of the program, and has been running quite good show participation model of